The Third Five Year Plan of the Indian Union a Pictorial Presentation - Ministry of Information and Broadcasting (Ministry of Information and Broadcasting, 1965)
The Third Five Year Plan seeks to give a more precise content to the social objectives of the Constitution and represents a large advance towards their realisation. It takes into account the successes and the failures in the first two plans and sets the tasks to be fulfilled in the perspective of development over the next fifteen years and more, in the course of which period India’s economy must not only expand rapidly but must, at the same time, become self-reliant and self-generating. Towards the achievement of these objectives, the Third Plan represents the first stage of intensive development in which the nation sets out to achieve as much in five years as has been realised in ten years of the First and the Second Plan.
Ministry of Information and Broadcasting
Ministry of Information and Broadcasting